Innovation in Destination Marketing: Leveraging Visitor Satisfaction and Electronic Word-of-Mouth (E-WOM) for Competitive Advantage, Moderated by External Factors - Zulkieflimansyah; Muammar Khadafie (Journal of Multidisciplinary Science, 2025)
This study explores the role of innovation management in enhancing the marketing effectiveness of tourist destinations by analyzing the interplay between visitor satisfaction, Electronic Word-of-Mouth (E-WOM), and external moderators. Focusing on a rural village in Yogyakarta, the research evaluates how innovative digital marketing strategies such as social media marketing, SEO, and content marketing—can drive destination popularity through systematic innovation adoption. Employing a quantitative survey method, purposive sampling was used to select 200 respondents aged 20+ who visit the destination at least twice annually. Data were analyzed using PLS-SEM. The findings reveal that nine of eleven hypotheses significantly contribute to positive outcomes: content marketing innovation strongly influences E-WOM and visitor satisfaction, while SEO innovation impacts E-WOM, satisfaction, and social media marketing. However, the moderating effects of external factors on E-WOM and destination popularity were negligible. These results highlight the strategic importance of innovation in tourism service design, emphasizing the need to align services with evolving tourist expectations. The study also proposes future research to investigate how service landscape innovation can further enhance visitor satisfaction, offering actionable insights for managing innovation in destination marketing.